V.O.Sukhomlynskyi about the Role of Fairy Tale in the Social Life of Children - Mariya Krayeva (Pedagogical Discourse, 2013)
The article highlighted the role of fairy tale in the social life of children, its educational potential, resulting in the development of individualism in the manifestation of childrenʼs creativity is exposed. V.O. Sukhomlynskyi’s disclosure principle of the tale`s high wisdom and life-sustaining optimistism is characterized. The most rational ways of using it in the educational process are outlined. It is also noted that the word doesn`t only develop the child`s speech and mind, but it also has a great educational potential.